PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU PEREMPUAN YANG MELAKUKAN ABORSI DI KOTA NOPAN SETIA - Simanjuntak, Immanuel; Silalahi, Riandy Micael; Ginting, Cindy Br; Surbakti, Suryandi Pratama; Aritonang, Zico Ricardo (The Juris, 2024)
The rapid and massive development of technology has had an impact on society in Indonesia, both positive and negative, one of whom was affected by the progress of this era was a woman from Nopan Setia City. Developments in society in Indonesia, especially in NopanSetia City, in this case are heavily influenced by promiscuity and a lack of awareness of the dangers of free sex, which results in unwanted pregnancies that lead to abortion. This type of research is normative juridical and is closely related to other legal sources, namely reviewing library documents from secondary data, especially research journals, dissertations and other research. That basically the problem of abortion (abortion) which is categorized as a crime or criminal act is already in the Criminal Code, but based on various factors and certain reasons, one of which is safety reasons and related to human rights issues and the protection of children who are victims of abortion, so that become extensive regulations regarding the criminal act of abortion as regulated in Law Number 36 of 2009 concerning Health. Looking at the judge's considerations in the object of this research, namely one of the women from NopanSetia City, there was an element of deliberate intent committed by Sri HanniPatimah in carrying out an abortion (abortion) by referring to Article 341 of the Criminal Code, by looking at the elements of the existing criminal act and From the existing trial facts it can be concluded that the criminal act existed and was carried out intentionally.